The cost and benefit analysis of climate change adaptation strategies among smallholder crop producers in the case of Sekela district, West Gojjam zone, Ethiopia - Yaregal Tilahun (Taylor & Francis Group, 2021)
Climate change has adversely affected the livelihoods of people in Ethiopia since a large proportion of the population is heavily dependent on agriculture as their adaptive capacities are perceived to be below. Therefore, this study aimed to identify determinants of farmer adaptation strategies with their costs and benefits of each adaptation strategy. The data were collected from 155 farm households using a random sampling method through semistructured questionnaires. The result of the multivariate probit model revealed that the likelihood of farmers to adopt adjustment of planting date, changing crop varieties, intercropping, crop rotation, irrigation, and minimum tillage were 51.6%, 61.9%, 56.1%, 38.1%, 10.3%, and 27.1%, respectively. The joint likelihood of using all adaptation strategies was 4.2%, while their failure to adopt all the adaptation strategies was 9.8%. Among the given adaptation options, intercropping, adjusting planting dates, crop rotation, and changing crop varieties are economically viable climate adaptation strategies. Regarding the intensity of adaptation, 78% of sampled respondents were used more than one adaptation option, and their NPV and BCR were higher when they used at least one adaptation option. Farmers who did not adopt any adaptation options were able to receive the lowest income per unit production. The study recommends that households should use multiple combinations of adaptation practices rather than the use of a single adaptation option. Thus, the government and stakeholders must provide educational and extension service, training, and updated climate information to smallholder crop producers to use and select the best and combination of adaptation strategies.